Pathogenicity of Streptococcus iniae causing mass mortalities of yellow catfish (Tachysurus fulvidraco) and its induced host immune response - Xu, Hongsen; Zhu, Nengbin; Chen, Yiling; Yue, Huamei; Zhuo, Meiqin; Wangkahart, Eakapol; Liang, Qianrong; Wang, Rui (Frontiers in Microbiology, 2024)
The outbreak of mass mortality occurred in Tachysurus fulvidraco farm in Hubei province of China. The pathogenic strain of Streptococcus iniae (termed 2022SI08) was isolated and identified from diseased T. fulvidraco, based on morphological, physiological and biochemical characteristics, as well as 16S rRNA gene sequence and phylogenetic analysis. Further, the whole genome of isolate S. iniae was sequenced and predicted to contain one single circular chromosome of 1,776,777 bp with a GC content of 37.14%. The genomic sequence analysis showed that 2022SI08 was positive for 204 virulent and 127 antibiotic resistant genes. The experimental challenge demonstrated the high pathogenicity of the retrieved isolate of S. iniae, with a median lethal dosage (LD50) 9.53 × 10 5 CFU/g. Histopathological examination indicated that the 2022SI08 strain could induce extensive tissue cell degeneration, necrosis, haemorrhage and inflammation in the skin, gill, fin, spleen, liver, kidney, intestine, eye and brain. Moreover, the innate immune enzyme activities in serum such as acid phosphatase and alkaline phosphatase were increased significantly at 24 and 48 hours post infection (hpi) and then decreased at 168 hpi. The transcriptional profile of immune associated gene in T. fulvidraco following bacterial infection was detected at each point of time, and the results revealed clear transcriptional activation of those genes, which proving their reacting and regulatory role during the response of the host against S. iniae infection. The results revealed that S. iniae was an etiological agent in the mass mortalities of T. fulvidraco and this research will be conducive for increasing our understanding on pathogenesis and host defensive system in S. iniae invasion.